Transcriptome Characterization of Gnetum parvifolium Reveals Candidate Genes Involved in Important Secondary Metabolic Pathways of Flavonoids and Stilbenoids - Deng, Nan; Chang, Ermei; Li, Minghe; Ji, Jing; Yao, Xiamei; Bartish, Igor V.; Liu, Jianfeng; Ma, Jing; Chen, Lanzhen; Jiang, Zeping; Shi, Shengqing (Frontiers in Plant Science, 2016)
Gnetum is a small, unique group of Gnetophyta with a controversial phylogenetic position. G. parvifolium is an important Chinese traditional medicinal plant, which is rich in bioactive compounds such as flavonoids and stilbenoids. These compounds provide significant medicinal effects, mostly as antioxidant, anticancer and antibacterial agents. However, the mechanisms involved in the biosynthesis and regulation of these compounds in G. parvifolium are still unknown. In this study, we found that flavonoid and stilbene compounds accumulated at different levels in various tissues of G. parvifolium. We further obtained and analyzed massive sequence information from pooled samples of G. parvifolium by transcriptome sequencing, which generated 94,816 unigenes with an average length of 724 bp. Functional annotation of all these unigenes revealed that many of them were associated with several important secondary metabolism pathways including flavonoids and stilbenoids. In particular, several candidate unigenes (PAL-, C4H-, 4CL- and STS-like genes) involved in stilbenoids biosynthesis were highly expressed in leaves and mature fruits. Furthermore, high temperature and UV-C strongly induced the expression of these genes and enhanced stilbene production (ie. resveratrol and piceatannol) in leaves of young seedlings. Our present transcriptomic and biochemical data on secondary metabolites in G. parvifolium should encourage further investigation on evolution, ecology, functional genomics and breeding of this plant with strong pharmaceutical potential.